A study on exterior beam to column joint with alternative ductile detailing - Banu, W. Balkis; Jaya, K.P. (Journal of Structural Engineering, 2024)
In seismically vulnerable areas, the beam to column joint is the most critical region in reinforced concrete structures.Because of the long development lengths and large bend diameters, the arrangements for straight bar and hookanchorage in structural concrete create practical problems. Proper anchorage and joint details of reinforcement areessential. The innovative joint designs that can reduce congestion of reinforcement in the joint are desirable. Thepresent study aims to compare the behaviour of exterior beam-column joint with the use of the threaded bar and steelfibers in place of conventional joint detailing. Six joint sub assemblages were tested under reversed cyclic loading.The displacement-controlled reverse cyclic loading was applied at the free end of the beam. A 3D numerical modelhas been created using the ABAQUS 6.14 software. The Concrete Damage Plasticity (CDP) model was used to definethe non-linear features of concrete by analyzing the response of the structure. The performance of an alternative jointdetailing, which is practically feasible, is compared with that of a conventional ductile detailing in terms of ultimateload, hysteresis behaviour, crack pattern, energy dissipation, and ductility. The average difference between FEA resultsand experimental results was less than 5%.